The Effect of Eight Weeks of Home based Combined Training with Red Grape Juice Supplementation on Quality of Life in Women with Multiple Sclerosis - Amin Jalili Sarqaleh; Mohammad Azizi; Kianosh Khamoshyan (Tehran University of Medical Sciences, 2022)
Background and Aim: Multiple Sclerosis is a chronic disease of myelin sheath degradation that reduces the quality of life in patients. Recent studies emphasize on the effect of exercise and natural supplements on the improvement of disease symptoms and quality of life. The aim of this study was to evaluate the effect of eight weeks combined training at home with red grape juice supplementation on quality of life in women with Multiple Sclerosis. Materials and Methods: In this study, 48 women with MS in the age range of 20-40 years were voluntarily selected and divided into 4 groups: training (n=12), supplement (n=12), training+supplement (n=12) and control (n=12). Combined training included 8 weeks and 3 sessions per week for 60 minutes of endurance  and resistance training with an intensity of 10-12 rate of perceived exertion. Subjects consumed 250 cc of grape juice supplement with 68% concentration for 8 weeks, 3 times a week. The control group engaged in their daily activities. Quality of life was measured with standard questionnaire (WHOQOL-BREF) 48 hours before and after the end of the study. Results: Eight weeks of intervention made a significant change in the quality of life. Based on the correlation t the results were as follows training groups (P=0.001)(7.1%), supplement (P=0.001)(10.5%) and training+supplement (0.000), There was a significant difference between the pre-test and the post-test (P≤0.05). But the changes in the training+supplement group were more than the other groups (P=0.000)(13.3%). In addition, based on the results of one-way analysis of variance, the amount of changes between the groups was also significant (P≤0.05). There was a significant difference between the training group and the control group, supplement group and supplement+training group (P≤0.05). Also, the supplement group had a significant difference with the exercise group and the control group, but there was no significant difference with the supplement + training group (P≥0.05). A significant difference was observed in the supplement+training group with all groups except the supplement group (P≤0.05). Conclusion: According to the results of the present study, women with Multiple Sclerosis can use combined training at home with red grape juice supplement to improve their quality of life.